Radiation dose to the eye lens and the shielding efficacy of a protective eye mask in patients with Hodgkin lymphoma undergoing repeated CT examinations - Rhee, Do-Byung; Yeo, Jin-Seok; Kim, Hyo-Gi; Bae, Il-Hwan; Kim, Hee-June (Radiation protection dosimetry, 2025)
This study evaluated radiation dose to the eye lens and the shielding efficacy of a radiation-protective eye mask (E-Mask) during repeated chest and abdomen computed tomography (CT) scans. Dose measurements were obtained using an anthropomorphic phantom and an optically stimulated luminescence dosemeter (Model TOPAZ, LANDAUER, USA). A 5-y follow-up scenario for Hodgkin lymphoma was simulated by assuming one scan per quarter, with the single-scan dose multiplied by 20 to represent four scans annually over 5-y. Despite the use of low-dose protocols based on national diagnostic reference levels issued by the Korea Disease Control and Prevention Agency, unshielded cumulative lens doses reached 363.89 mSv (right) and 424.84 mSv (left). Using an E-Mask reduced these doses to 243.96 mSv and 240.13 mSv, corresponding to reductions of 32.96% and 43.48%, respectively. These findings support the use of the E-Mask in radiosensitive populations to reduce lens exposure during long-term CT follow-up.